Characteristic evaluation of 20-Bit consecutive codes in high performance optical burst mode receiver configuration - Adibah Mazwar; Azura Hamzah; Sevia Mahdaliza Idrus; Atsushi Kanno; Norliza Mohamed (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Optical burst mode receivers are indispensable components for Passive Optical Network (PON) and Ethernet Optical Access Network (E-OSAN). An optical burst mode receiver with transfer function Gn(jω/ω0) = 1 - Hn(jω/ω0) is proposed, of which better performance is anticipated than that of conventional AC-coupling. Next, an optical burst mode receiver with fast response Gn(jω/ωF) and slow response Gn(jω/ωS), whereby Gn(jω/ωF) switches to Gn(jω/ωS) right after the DC component of the input burst signal converges to 0 is proposed. Then, an automatically switching circuit that switches fast response Gn(jω/ωF) to slow response Gn(jω/ωS) circuits right after the maximum peak value of the output burst Gn(jω/ωF) is 1/2 and the DC components of the input burst converges to 0 is also proposed. This paper presents the experiments on same consecutive codes in burst mode receivers using the proposed automatically switching circuit, with evaluation on its characteristics made through simulation.